Communication Channel Effectiveness in Digital Tourism Communication: A Media Ecology Theory Perspective on Karuing Tourism Village - Ni Nyoman Ayu Wilantari (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2026)
Advances in digital technology have transformed communication patterns in the promotion of tourist destinations, including in tourism villages that highlight local wisdom as their main attraction. This study aims to analyze the effectiveness of communication channels in promoting the Karuing tourism village from the perspective of media ecology theory. The study employed a descriptive quantitative approach using a survey method involving 50 respondents, consisting of tourists and local residents familiar with the promotional activities of the Karuing tourism village. Data collection was conducted using a questionnaire with five indicators of communication channel effectiveness: accessibility, immediacy, interactivity, cultural resonance, and engagement. The data were analyzed using SPSS version 26 to describe the level of effectiveness for each indicator. The results show that all indicators fall into the “effective” category. The Engagement indicator received the highest average score (4.45), followed by Cultural Resonance (4.36), Accessibility (4.28), Immediacy (4.20), and Interactivity (4.05). These findings indicate that authentic representations of local culture and the ability of digital media to foster emotional engagement are key factors in the success of tourism communication in Karuing Tourism Village. From the perspective of media ecology theory, digital media not only serves as a means of conveying information but also shapes a communication environment that connects communities, culture, and tourists within a sustainable communication ecosystem. This study makes a conceptual contribution by deepening the understanding of the effectiveness of communication channels based on local culture as a strategy for the sustainable development of tourism villages.